Bribery and implicit agreements: A reply to Philips - Carson, Thomas L. (Journal of business ethics, 1987)
The author has elsewhere defended the view that accepting a bribe involves the violation of an implicit or explicit promise or understanding associated with an office or position that one occupies and that therefore it is prima facie wrong to accept a bribe. Michael Philips has criticized this position in a recent paper. He argues that (a) there are cases in which accepting a bribe violates no promises or agreements, and (b) there are cases in which there is no prima facie duty to refuse an offer of a bribe. The author offers replies to both of these objections.